Power, politics and exploration in Fascist Italy : The 1928 Watershed - Marco Cuzzi (Routledge, 2023)
In the 1920s and 1930s, a series of scientific, sportive, archaeological and geographical enterprises were undertaken, aimed at establishing a specific and central role for Italy in the international panorama. In the 1920s, Nobile’s Arctic and Karakorum expeditions fitted fully into this overall plan, and so did Italian geographical exploration and archaeological missions in Libya and the new season of archaeological missions in Asia inaugurated by Giuseppe Vincenzo Tucci in Tibet in 1933 and 1936. This chapter considers these exploits in relation to the emergence of a fascist politics of power in the late 1920s and the Italian foreign political agenda. Ambiguous plans to integrate Italy into a set of European agreements and negotiations – the French-German axis, negotiations for France-Italy disarmament, closer Mediterranean ties with London – coexisted with the idea of alleged Italian difference and its disruptive role in the Old Continent’s economic-social and political-diplomatic equilibria. A combination of fascist universalism and internationalist doctrines led Italy in the direction of more aggressive initiatives, such as the intervention in Spain, the Rome-Berlin Axis and the attack on Ethiopia. Outside Europe, in 1937, the regime signed the Asian pact between Turkey, Persia, Iraq and Afghanistan to limit the Soviet and British presence in the region.